Conformational and physicochemical properties of Abametapir using density functional theory - Dhungana, Santosh; Mallik, Hari Sankar; Lamichhane, Tika Ram; Giri, Subash; Dhungana, Siddharta; Lamichhane, Hari Prasad (Scientific World, 2025)
Abametapir is a newly approved topical lotion for the treatment of head lice. This molecule is analyzed in the gas phase, as well as in non-polar solvent CCl4 and polar solvent water, using Density Functional Theory with the B3LYP/6-311+G(d) exchange-correlation functional in Gaussian 16 software. The optimized molecule has two benzene rings lying in a plane with one carbon atom of each ring is replaced with a nitrogen atom. On scanning energy with respect to the vibration of dihedral angle C4–C5–C8–N9 with 10° step in the entire dihedral angle shows the possibility of the two conformers, one of which has 99.99% occurrence at the room temperature. The FTIR, Raman and UV-visible spectra of the optimized molecule of the more stable conformer were calculated in different solvents and gaseous states. Among many modes of vibration, the bending vibration of H16-C1-H17 contributes notably to the intense FTIR signal at 1510 cm-1, with a Potential Energy Distribution contribution of 52%. The highest value of Raman intensity at 1636 cm-1 is attributed to the stretching mode of C12-C13 (61%). The most intense peak of the UV-visible spectra of the molecule shifted from 281 nm in the gas phase to 288 nm in the CCl4 and water solvents. Analysis of the HOMO-LUMO in different solvents and gas provided insights into the molecule's chemical stability and reactivity. This molecule has strong electrophilic behavior in both gas and solvent phases.